Analyzing the impact of the oil phase selection and curcumin presence on the nanoemulsion stabilizing layer using electron paramagnetic resonance spectroscopy - Djoković, Jelena; Demisli, Sotiria; Papadimitriou, Vassiliki; Xenakis, Aristotelis; Savić, Snežana (Archives of Pharmacy, 2022)
The stabilizing layer of nanoemulsions impacts their stability and destiny upon in vivo administration. The aim of this work was to gain information about the dynamics of the surfactants’ monolayer when different oils (soybean / fish) were used, and obtain data regarding the localization of curcumin, an active compound with many potential health benefits, using electron paramagnetic resonance (EPR) spectroscopy. Formulations were analysed using EPR technique with three different spin probes: 5-, 12- and 16-doxyl stearic acid (DSA), to investigate membrane dynamics at different depths. The results indicated that the oil type played a crucial role, not only on the structure, but also in the localization of the bioactive compound. The addition of curcumin changed the rotational correlation time (τR) values, most notably for 5-DSA, both in soybean oil and fish oil nanoemulsions, indicating its localization in the stabilizing layer, but with opposite effects. In the soybean oil nanoemulsion the addition of curcumin increased spin probe mobility, with τR decreasing from 2.18±0.60 ns to 1.66±0.61 ns, indicating a less rigid stabilizing structure, while in the fish oil formulations it resulted in a more rigid structure reflected in τR increase from 1.19±0.10 ns to 2.96±0.81 ns and 1.63±0.13 ns to 2.27±0.19 ns, for 5-DSA and 12-DSA, respectively. This study concluded that the curcumin is located in the stabilizing layer of nanoemulsions, but its impact on stabilizing layer structure depended on the oil phase selection, with particular stabilizing effects on fish oil nanoemulsions.